Predicting the Potential Applicability to Other Technical Fields Through the Linkage Between Backward and Forward Citations - Hirose, Masayuki (Frontiers in Research Metrics and Analytics, 2021)
This article is a modest attempt to shed some light on the question of linkages between backward and forward citations in technical fields posed by Trajtenberg et al. (1997). They found interesting similarities and high correlations between equivalent measures looking forward and backward. They also implied the linkage between distant backward and distant forward citations. There are several questions to be posed in applying their insights to Japanese patent applications, however, due to the differences in the patent classification system and the subject of citation, i.e., citations by the applicant or examiner, between the US and Japan. In addition, and most importantly, the possibility that subsequent classifications may match, even if the first classification is different, is unavoidable with existing measurement methods of technical distance. In order to investigate these research questions, the author proposes a new measurement method for the technological proximity between examiner’s citations and their originating patents using IPC-based patent classifications. Using such a proposed method, the author created two hypotheses and tested them for about 14,000 examined patent applications filed in 2008 with the JPO. As a result of testing Hypothesis I, the author confirmed that Trajtenberg et al.’s insights can be applied to Japanese patent applications using citations by the examiners and IPC-based patent classifications. In other words, it was confirmed that patent applications citing backward citations categorized in a technical field distant from the invention are more likely to be cited by forward citations categorized in a technical field distant from the invention. As a result of the verification of Hypothesis Ⅱ, it was further confirmed in some technical fields that the backward citations categorized in a technical field distant from the invention are more likely to be in the same technical field as the forward citations categorized in a technical field distant from the invention. The author believes that these verified results indicate the possibilities of using backward citations as a starting point from which we can find patent applications for inventions at an early stage with potential applicability to other technical fields.